1984
DOI: 10.1104/pp.74.3.499
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Phloem Bleeding from Cryopunctured Fruits of a Ureide-Producing Legume

Abstract: The vasculature of the dorsal suture of cowpea (Vigna uagwicalata IL.] Walp) fruits bled a sugar-rich exudate when punctured with a fie needle previously cooled in liquid N2. Bleeding continued for many days at rates equivalent to 10% of the estimated current sugar intake of the fruit. A phloem origin for the exudate was suggested from its high levels (0.4-0.8 millimoles per milliliter) of sugar (98% of this as sucrose) and its high K' content and high ratio of Mg2e to Ca2l. Fruit cryopuncture sap became la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Second, the estimates in the present study compare favorably with values obtained in other studies. The estimated concentrations of amino acids in the phloem sap of black mustard (77-216 mM) (Table 3) are similar to those measured in the phloem sap of a variety of herbaceous plant species (112-1600 mM) (Barlow and Randolph, 1978;Fukumorita and Chino, 1982;Pate et al, 1984;Fisher and Gifford, 1986;Weibutl, 1988). Similarly, estimated sugar concentrations (19.1-25.8%) ( Table 3) fall within the range recorded in herbaceous plants (4.3-30.8%) (e.g., Pate, 1973;Pate et al, 1974;Fukumorita and Chino, 1982;Fisher and Gifford, t986;Ohshima et al, 1990).…”
Section: Discussionsupporting
confidence: 50%
“…Second, the estimates in the present study compare favorably with values obtained in other studies. The estimated concentrations of amino acids in the phloem sap of black mustard (77-216 mM) (Table 3) are similar to those measured in the phloem sap of a variety of herbaceous plant species (112-1600 mM) (Barlow and Randolph, 1978;Fukumorita and Chino, 1982;Pate et al, 1984;Fisher and Gifford, 1986;Weibutl, 1988). Similarly, estimated sugar concentrations (19.1-25.8%) ( Table 3) fall within the range recorded in herbaceous plants (4.3-30.8%) (e.g., Pate, 1973;Pate et al, 1974;Fukumorita and Chino, 1982;Fisher and Gifford, t986;Ohshima et al, 1990).…”
Section: Discussionsupporting
confidence: 50%
“…Here, as suggested earlier ( 17), the major xylem-borne nitrogenous solutes, ALA and ALA, were readily metabolized (Table III), and the extent of direct xylem-to-phloem transfer remained uncertain. In cowpea, a species that also exports principally ureides from root nodules, investigations using aphids (3) and cryopunctured fruits (16) Previous research has shown that the concentration of xylem-borne amino acids is an important factor in the uptake and distribution pattern in tomato (22) and cottonwood (23) stems. Therefore, we supplied ureido and amino compounds at high specific activity against the background of the solutes that are normally delivered from nodulated roots to shoots in the xylem stream.…”
Section: Xylem-to-phloem Transfer Of Xylem-borne [14c] Nitrogenous Somentioning
confidence: 99%
“…The media contained a high concentration (0.38M) of sucrose and glutamine which were known to stimulate androgenesis in anther culture (Keller et al,1975) and potassium nitrate as a presumed source of nitrogen. On the other hand, the exudate of cowpea fruits from phloem origin contained 0.4-0.8 M of sucrose (Pate et al, 1984). Recently, Ilic-Grubor et al (1998b) Other components were the same as those in NLN-13 medium (Keller et al,1987).…”
Section: Introductionmentioning
confidence: 82%